Legal Politics of Religious Moderation and State Defense Policy at Public Universities - Muhammad Shohibul Itmam; Abdelmalek Aouich (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
This study aims to discuss the policy of the Ministry of Religious Affairs through the Sub Directorate of Islamic Religious Education at Public Universities (PTU) in forming Griya Moderasi Beragama dan Bela Negara (MBBN) to strengthen the understanding of religious moderation and eliminate religiousness that often legitimizes violence as a manifestation of religious teachings during the rise of groups that claim to be the most correct. This study uses doctrinal law, political law, and critical analysis approaches. Data analysis was conducted by exploring moderation policy documents and legislation products. This study found that the legal politics of Religious Moderation and State Defence at PTU is a strategic government policy to strengthen the nation's life amid legal and religious plurality in the face of confrontation with radicalism groups. The government's strategic policy is synergized with national development, accelerating the realization of justice and welfare. The policy is also a firm step by the Indonesian government in contributing to the world according to the demands and developments of diversity in the era of globalization, especially in counteracting the massive movement of radicalism and intolerance in Indonesia.